An overview of endoscopic stapedotomy in a tertiary care centre - Gujrathi, Atish B.; Shroff, Siddharth A.; Gadpayale, Nishikant; Agarwal, Naman (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Stapedotomy is now one of the most popular and common surgeries done worldwide. Otosclerosis remains the most common single cause of conducting hearing loss in adult population. Females are more frequently affected than males with an approximate 2:1 ratio. Methods: This study consists of 30 patients who underwent stapedotomy for otosclerosis. This study was conducted at Dr Shankarrao Chavan Government Medical College, Nanded, during the period of 2 years (2017-2019). Patients were evaluated and operated. The various anatomical variations, diagnostic dilemmas, intraoperative complications, its management and follow-up were done systematically. Results: Age of patients included in this study ranged from 15 to 50 years. Youngest patient was a 17-year-old male. Age of presentation was most commonly seen in third decade of life. Male to female ratio was 1:2. The most common symptom was hard of hearing followed by tinnitus. In this study, 76.67% of the patient’s had bilateral disease. 66.66% of patients had hearing loss between 41-55 dB with mean pre-operative pure tone average was 51.16 dB. About 80% of patients had successful air bone closure between 0-10 dB after the surgery. Conclusions: Endoscopic stapedotomy seems a feasible and relatively safe surgical technique in limited case series. Cosmetically this procedure was more compliant by the patients however endoscopic stapedotomy requires a significant learning curve and an extreme expertise.